Empowering China’s sustainable development through social-ecological networks - Wuyang Hong; Yelin Li; Renzhong Guo; Bin Chen; Wenjia Zhang; Feixue Li; Shuwen Yang; Yuke Liu; Yingmei Zhao; Yurui Li; Shengbiao Wu; Biao He (npj Urban Sustainability)
Abstract The ongoing reform of China’s spatial planning system significantly influences the achievement of Sustainable Development Goals. By fostering positive economic, social, and environmental interactions among cities, China has gradually established a coupled-networks to coordinate economic and ecological development. However, the current planning evaluation research usually focuses on the interior of the city, and lacks the evaluation of the planning convergence between different cities the integrity of this coupling deployment across different cities remains unclear. We conducted a systematic evaluation of China’s territorial spatial planning documents (encompassing 2715 county-level administrative units), constructing inter-urban socio-ecological networks by employing cities and districts as nodal units, with development-oriented partnerships and conservation-focused alliances explicitly stipulated in planning policies serving as social and ecological edges respectively. These networks were subsequently compared against multiple networks derived from land use/cover change (LUCC) analyses through multidimensional comparative analysis. Results show that 69.5% of the planned networks are supported by LUCC data; however, 10.4% of county nodes were overlooked by the spatial plans. Therefore, a broader city/county network should be constructed with a focus on poverty-stricken counties that have fewer opportunities, while also strengthening cooperation with bordering countries to improve the stability and completeness of the intercity network. This study provides a reference blueprint for sustainable city construction worldwide, particularly in developing countries.